Giáo trình anh văn ngoại thương 2 - Lưu, Nguyễn Quốc Hưng (Trường Đại học Cần Thơ, 2007)
The course has two aims: - To provide language practice in international trade context that will be directly relevant to the students real needs; - To encourage fluency and the active use of English.